Sea to land wireless characterization - Ong, Yu Ying. (2012)
This project is a collaboration between Nanyang Technological University (NTU) and Singapore Technologies Electronics Limited, to investigate and characterize the channel for non-line-of-sight (NLOS) propagation in sea environment. Trials were conducted at the Changi SAF Yatch Club based on transmitting frequency of 5.5 GHZ, modulated using Binary Phase Shift Keying (BPSK) technique and spread using Direct Sequence Spread Spectrum (DS-SS) technique. The system used in this project is a 2x2 multiple-input multiple-output (MIMO) system.